The Prevalence of Fatty Liver Disease and Its Associated Factors Among Dayak Community in Kuching and Samarahan Division, Sarawak - Azlan Arif, Bolen; Jeffery, Stephen; Cheah, Whye Lian; Koa, Ai Jiun (UPM, 2025)
Introduction: Globally, fatty liver disease (FLD) shows a worrying pattern of substantial increase in prevalence from year 1990 to 2020. Despite this, there are limited studies on FLD in Malaysia where the FLD trend remained unascertained. In Sarawak, there is a particular concern on FLD in Dayak Community due to the increase in obesity trend among this community, which is known as one of the factors of FLD. Thus, this study aims to determine the prevalence of FLD and its associating factors among the Dayak community in Kuching and Samarahan divisions. Materials and methods: This study was a cross-sectional study with a cluster sampling conducted among 281 respondents. Data were collected through questionnaires, and ultrasound assessments was used to diagnose FLD, then data was analyzed with SPSS version 29.0. Results: The respondent's mean (SD) age was 52.5 (16.00) years old. Analysis revealed that 47.3% of the respondents had FLD. Most of the FLD were in the mild stage (69.9%), and none of the respondents were in the severe stage. Bivariate analysis revealed that the age group of 35 to 65 years (p<0.01), the overweight and obese group (p<0.001), the presence of comorbidities (p<0.05), and the presence of alcohol consumption (p<0.05) appeared to be significant predictors of FLD. Conclusion: The prevalence of FLD among the Dayak community in Kuching and Samarahan divisions was higher in comparison to previous studies which indicate an urgent needs of actions from the relevant departments.